Surgical Management of Mucocele of The Lower Lip : Case Report and Literature Review - Ichi, Ericko; Saputra, Dwi Riski; Rahayu, Luh Dewi (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Surgery for mucocele cases in daily practice is still a challenge. Mucocele is a lumpy lesion in the oral cavity that can interfere with the patient's comfortable speaking and chewing process. A mucocele is a lump in the oral cavity due to rupture of the minor salivary glands due to trauma or obstruction of the minor salivary glands. The prevalence of mucocele is 2.4 cases out of 1000 people, and it often occurs at a young age. This paper aims to describe and report mucocele management with simple surgery. Case: A 20-year-old patient was reported to have a mucocele in the left inferior labial region. The lump has been there for two months and is slowly getting bigger. The lump is painless and very annoying when talking and chewing. Conclusion: Dental practitioners can carry out mucocele management with correct diagnosis and simple surgical methods with minimal equipment to ensure better treatment results.